Response of white clover genotypes to evaluation environments of dense and spaced planting, and implications for selection - Annicchiarico, P; Piano, E (Euphytica, 2000)
Twelve genotypes were grown for two years asmonocultures in the evaluation environments (EE) ofspaced planting (SP) and dense planting (DP). Drymatter (DM) yield, seed yield and their contributingtraits were recorded. The environments were comparedfor: i) genotype performance, and selection efficiencyfor the target environment of DP, and ii) estimates ofgenetic correlations between traits. DP was obtainedby close transplanting of clonal cuttings. EE × Ginteraction occurred for DM yield over harvests, andstolon density, petiole length, inflorescenceproduction and number of florets per inflorescence averagedover repeated measurements. Interaction effectsleading to relatively higher DM yield in SP tended tobe associated positively with those for the othertraits and featured the genotypes with greater abilityto colonize bare soil by stolon production. Theinteraction effects decreased with time and generallydisappeared (p < 0.05) by the end of the experiment,when the environments reached a similar DM yield andstolon density. EE × G interaction also occurred forseed yield (p < 0.08), recorded at the second year.Indirect selection in SP for performance in DP waspredicted to be less efficient for DM yield (-40%),seed yield (-23%) and the other traits subject to EE ×G interaction, compared with direct selection in DP.Evaluation under SP led to identification of severalgenetic correlations that were not confirmed under DP.DP compared with the traditional SP evaluationtechnique is more labour-demanding but allows for i)increasing the selection efficiency and/or decreasingthe time needed for a reliable evaluation, and ii)obtaining a more reliable estimation of geneticcorrelations for ordinary agricultural environments.[PUBLICATION ABSTRACT]